Investigation of prostate resected weight on postoperative sexual dysfunction following transurethral resection of prostate surgery: a population-based study - Liu FC; Shen SJ; Lin JR; Yu HP (Dove Medical Press, 2019)
Fu-Chao Liu,1,2,* Shih-Jyun Shen,1,2,* Jr-Rung Lin,1–3 Huang-Ping Yu1,2,4 1Department of Anesthesiology, Chang Gung Memorial Hospital, Taoyuan, Taiwan; 2College of Medicine, Chang Gung University, Taoyuan, Taiwan; 3Clinical Informatics and Medical Statistics Research Center and Graduate Institute of Clinical Medicine, Chang Gung University, Taoyuan, Taiwan; 4Department of Anesthesiology, Xiamen Chang Gung Hospital, Xiamen, China *These authors contributed equally to this work Background: Benign prostate hyperplasia, a common disease in elderly men, can be surgically treated with transurethral resection of the prostate (TURP). Postoperative sexual dysfunction is a major issue and is influenced by many factors. The present study aimed to assess whether the intraoperative resected prostate weight influences the probability of postoperative sexual dysfunction.Methods: This population-based study included 41,574 patients from the Nation Health Insurance Research Database who had undergone TURP once between 1997 and 2013. All patients were divided into three groups according to the resected prostate weight (low, medium, and high groups). Perioperative risk factors influencing sexual function were analyzed. The chi-squared test and Fisher’s exact test were used to analyze differences in demographic data. The Cox proportional hazard regression analysis was used to analyze the HRs. All statistical analyses were two-sided, and a P-value <0.05 was considered statistically significant.Results: Of the 41,574 patients, 1,168 had postoperative sexual dysfunction after surgery. The incidence was not significantly different among the three resected prostate weight groups. Younger patients and patients with histories of chronic renal disease, ischemic heart disease, and obesity had higher prevalence of postoperative sexual dysfunction. Additionally, the onset time of sexual dysfunction was not significantly different among the three resected prostate weight groups.Conclusion: Among patients undergoing TURP in Taiwan, the resected prostate weight does not seem to be related to the presence or onset time of postoperative sexual dysfunction. Keywords: benign prostate hyperplasia, new-onset postoperative sexual dysfunction, population-based study